2006
DOI: 10.1007/s10734-005-8608-x
|View full text |Cite
|
Sign up to set email alerts
|

Academics’ views on publishing refereed works: A content analysis

Abstract: Survey research was carried out with academics (N=205), from a large regional Australian university, to explore their views about publishing or not publishing in refereed sources and their perceived worth of this activity. Several open-ended questions were included in the survey to elicit information about the factors that either encourage or discourage these academics from publishing. Additionally, questions were posed to allow the respondents to discuss ways that the University could further support them in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Whilst there is certainly a growing research-informed body of literature relating to research and researchers, and the interaction between the two (e.g. Åkerlind 2008; Coleridge et al 2004;Drnach 2002;Fairweather 2002;Fox 1992;Fox and Mohapatra 2007;Hemming et al 2007;Manathunga et al 2007;McGrail et al 2006;Rath 2009;Wimsatt et al 2009), we know relatively little about how researchers (particularly academics as researchers) conduct their work and what attitudes they hold towards it, and about the nature of their development and the process(es) whereby it occurs. Moreover, research emanating from Europe, and relating to European contexts, is under-represented.…”
Section: Understanding Researcher Developmentmentioning
confidence: 99%
“…Whilst there is certainly a growing research-informed body of literature relating to research and researchers, and the interaction between the two (e.g. Åkerlind 2008; Coleridge et al 2004;Drnach 2002;Fairweather 2002;Fox 1992;Fox and Mohapatra 2007;Hemming et al 2007;Manathunga et al 2007;McGrail et al 2006;Rath 2009;Wimsatt et al 2009), we know relatively little about how researchers (particularly academics as researchers) conduct their work and what attitudes they hold towards it, and about the nature of their development and the process(es) whereby it occurs. Moreover, research emanating from Europe, and relating to European contexts, is under-represented.…”
Section: Understanding Researcher Developmentmentioning
confidence: 99%
“…Åkerlind, 2008;Blackburn & Lawrence, 1995;Hemmings, Rushbrook, & Smith, 2007;Ito & Brotheridge, 2007). Across a number of decades, this work has shown that various factors are associated with, and/or predict, research output.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ramsden's (1994) survey of 890 staff in 18 Australian higher education institutions revealed that the group with the highest activity in research was five times more productive than the least active group. In most studies about academics' research performance, time constraints was frequently cited as impeding research engagement and outputs (Borg 2007;Hemmings, Rushbrook, and Smith 2007;Griffiths, Thompson, and Hryniewicz 2010).…”
Section: Providing Sufficient Time Involvement In Researchmentioning
confidence: 99%
“…Despite differences in the conceptualisation of culture, general findings from studies in the field have been that a supportive and stable work environment would facilitate academics' research productivity, and a lack of research culture is frequently identified as the impediment to research productivity. Thus, fostering a nurturing research environment and providing support are perceived as critical to improving the research performance of academics (Baird 1994;Pratt, Margaritis, and Coy 1999;Hiep 2006;Hemmings, Rushbrook, and Smith 2007). Adopting the definition of culture by Williams, Dobson and Walters (1993), Pratt, Margaritis, and Coy (1999) reported how an originally teaching-dominated school of management in a New Zealand university successfully developed a rich research culture by changing the beliefs of faculty members.…”
Section: Developing a Rich Research Culturementioning
confidence: 99%